Odpowiedzi

2010-01-25T18:48:53+01:00
A) 48a²-10a+4a+a² dla a=-1/7
49a²-6a dla a=-1/7
49×(-1/7)²-6×(-1/7)=1,8
b)-12√c-c-8c+13√c dla c=4
√c-9c dla c=4
√4-9×4=-34

1 5 1
Najlepsza Odpowiedź!
2010-01-25T18:51:54+01:00
A)-(-48a(do potegi 2)+10a)-(-4a-a(do potegi 2)
48a(do potęgi 2)-10a+4a+a(do potegi 2 )
49a(do potęgi 2)-6a
49 x (-1/7)(do potęgi 2)- 6 x (-1/7)= (49/1) x 1/49 + 6/7=
=1 + 6/7=1 6/7


b))-(12pierwiastek kwadratowy c-c)+(-8c+13 pierwiastek kwadratowy c)
-(12(pierwiastek kwadratowy 4-4) + (-8 x4 + 13(pierwiastek kwadratowy z 4)=
=-32+26=-6
2010-01-25T19:05:51+01:00
A)-(-48a²+10a)-(-4a-a²)= 48a²-10a+4a+a²=49a²-6a=49•(-1/7)²-6•(-1/7)=49•1/49-6•1/7=-6/7

b)-(12*2-√4)+(-8*√4+13*2)=-(24-√4)+(-8√4+26)=-24+√4-8√4+26=2+7√4